Hearing Glenn Gould's Body: Corporeal Liveness in Recorded Music - Sanden, Paul (Current Musicology, 2009)
Live music does not exist without its recorded other. In other words, the concept of liveness in music was unknown until there was something not live-recordings-with which to compare it. Sarah Thornton describes the conventional ideology of liveness, which derived from a live/recorded binarism, as historically giving "positive valuation to ... performed music. [The word 'live'] soaked up the aesthetic and ethical connotations of life-versus-death, human -versus-mechanical, creative-versus-imitative ... Liveness became the truth of music, the seeds of genuine culture. Records, by contrast, were false prophets of pseudo-culture" (1995:42). Liveness, at least as historically constructed, signified the authenticity of human musical production and performance, always considered in contrast with the artifice of electronic reproductions.